Ketogenic diet increases mitochondria volume in the liver and skeletal muscle without altering oxidative stress markers in rats. Issue 11 (November 2018) - Parry, Hailey A.; Kephart, Wesley C.; Mumford, Petey W.; Romero, Matthew A.; Mobley, C. Brooks; Zhang, Yufeng; Roberts, Michael D.; Kavazis, Andreas N.
Abstract: Ketogenic diets (KD) consist of high fat, moderate protein and low carbohydrates. Studies have suggested that KD may influence oxidative stress by affecting mitochondrial quantity and/or quality, and perhaps lengthen lifespan. Therefore, we determined the effects of KD on multi-organ mitochondria volume and oxidative stress markers in rats. Ten month-old male Fisher 344 rats (n = 8 per group) were provided with one of two isocaloric diets: standard chow (SC) or KD. Rats were euthanized if: a) vitality scores exceeded a score of 16, b) rapid weight loss, or c) veterinarian deemed euthanasia necessary. The median lifespan of rats was higher in KD (762 days) compared to SC (624 days). Citrate synthase activity (i.e. estimate of mitochondria volume) was higher in the liver (p = 0.034) and gastrocnemius (p = 0.041) of KD compared to SC. Liver superoxide dismutase 1 and catalase antioxidant protein levels were higher in KD, albeit not significant (p = 0.094 and p = 0.062, respectively). No significant differences in protein levels of other antioxidants or markers of lipid and protein oxidative damage were observed in either the gastrocnemius, liver, or brain. In summary, KD increased mitochondria volume in liver and gastrocnemius and median lifespan in rats. Additionally, our data show that the increase in mitochondrial volume occurred without changes in oxidative damage or antioxidant protein levels in the gastrocnemius, liver, or brain.